Awareness of occupational safety and health at Higher Education Institution in Malaysia / Lili Syahani Rusli and Mimi Sophia Sarbandi - Rusli, Lili Syahani; Sarbandi, Mimi Sophia (Research Management Institute (RMI), 2011)
The purpose of this study is to investigate how far the awareness on the occupational safety and health (OSH) policy from Higher Education Institutions for staff and students and to review on the weakness in occupational Safety and Health policy in Higher Education Institution and make recommendation based on research finding. During the study, a total of 100 respondent had responded to the questionnaire and the analysis was done on 78 respondent only, omitting 22 respondent who did not complete the questionnaire. The respondent are restricted to Klang Valley area because of time constrain. The awareness on OSH can be divided into 6 which are awareness on safety (utility), awareness on facility, awareness on safety (life), awareness on property, awareness on environment and awareness on safety (location). The highest awareness for both staff and students is awareness on environment and the least is awareness on safety (utility). As a conclusion, this reseach discuss how far the awareness among staff and students in occupational safety and health in Higher Education Institution.